PENGEMBANGAN MEDIA PIANGPO BERBASIS DIGITAL INTERAKTIF DALAM MENINGKATKAN LITERASI NUMERASI ANAK USIA DINI NAK USIA DINI - Amelyani Amelyani; Nita Priyanti; Hamid Patilima (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Early childhood numeracy literacy in Indonesia still faces significant challenges due to the dominance of conventional approaches, resulting in low student engagement. This study positions interactive video-based learning media as an innovative solution to enrich numeracy practices in early childhood education. The purpose of this research is to develop the interactive learning video Ã¢â‚¬Å“PIANGPOÃ¢â‚¬Â (Smart Numbers and Patterns), assess its feasibility, and test its effectiveness in improving numeracy skills among young children. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the development stage, involving 45 children in group B (ages 5Ã¢â‚¬â€œ6) at TK Al Husna, South Jakarta. Data collection instruments. included observation sheets, expert validation questionnaires, and numeracy assessment sheets, analyzed descriptively using qualitative and quantitative approaches. The results showed that the Ã¢â‚¬Å“PIANGPOÃ¢â‚¬Â video was highly feasible, with an average expert validation score of 4 on a 1Ã¢â‚¬â€œ5 scale. Its effectiveness was demonstrated by a significant improvement in childrenÃ¢â‚¬â„¢s numeracy scores, from 2.26 (Beginning to Develop) to 3.46 (Developing as Expected), and an increase in engagement levels from 74% to 92%. Therefore, Ã¢â‚¬Å“PIANGPOÃ¢â‚¬Â is proven feasible and effective as an innovative medium to enhance early childhood numeracy literacy.